Tanggung Jawab Bank Terhadap Pencurian Saldo Rekening: (Studi Di Bank BRI) - I Made Widiasmara; H. Djumardin Djumardin (Private Law, 2022)
This study aims to discuss two problems, namely the form of legal protection and responsibility and the bank's efforts in solving the problem of theft of account balances with customers. This study uses the Normative Empirical legal method by using the legal, conceptual and sociological approach. From the results of the study, it was found that the bank as a place to store funds is fully responsible and will compensate for all losses if it is true that the lost funds are caused by Skimming or Pishing and the settlement efforts use non-litigation channels by means of mediation based on the provisions of Bank Indonesia Regulation Number 10/1/PBI. /2008 amendment to Bank Indonesia Regulation Number 8/5/PBI/2006 concerning banking mediation.